Rekaman baru Scopellaria marginata (Cucurbitaceae) dari Malang, Jawa Timur, Indonesia - Arumingtyas, Estri Laras; Turhadi, Turhadi Turhadi; Azrianingsih, Rodiyati; Afiyanti, Mufidah; Pratami, Mentari Putri; Sudarjayanti, Briliyan Natalina; Solihah, Fifi Mar’atun (Jurnal Biologi Udayana; Vol 27 No 2 (2023): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2023.v27.i02.p06, 2023)
Scopellaria is a genus in Cucurbitaceae which only consists of two species, namely S. diversiflora and S. marginata . Both types have never been reported before in the East Java region. This study aimed to characterize naturalized Scopellaria marginata in Malang, East Java. Scopellaria marginata reported as new record for East Java, Indonesia with scarbid-hairy stems; denticulate leaf edges, rough-hairy on the adaxial leaves and coarsely hairy on abaxial parts; fruit shape varied, such as round (globose), oval (elliptic), and fusiform; seed size 3.0-4.4 mm, whitish, and edges distinctly square-margined. This species was found climbing on other plants and creeping above ground. Its description and distribution of this species are presented in this paper.